Temperature Dependance of the Energy Band Gap and Absorption Coefficient of Thin Films of Chemically Deposited Zinc Sulfide, Manganese Sulfide and Multilayer Zinc Sulfide-Manganese Sulfide - Varghese, Shaji; Iype, Mercy (Asian Journal of Chemistry, 2011)
Zinc sulfide (ZnS) and manganese sulfide (MnS) single layer thin films are deposited on glass substrates by chemical bath deposition technique. Multilayer ZnS-MnS thin films are also obtained by using MnS films as substrates for the deposition of ZnS films. These films are annealed in air at different temperatures. Optical studies are separately done on ZnS, MnS and multilayer ZnS-MnS films. Optical properties are studied (between 300-900 nm) in a UV-VISspectro photometer and the absorbance recorded as a function of photon energy. The optical band gap and maximum absorption coefficient of the as deposited and annealed samples are determined. Optical band gap and absorption coefficient decreases with annealing.